Stretchable Triboelectric Self‐Powered Sweat Sensor Fabricated from Self‐Healing Nanocellulose Hydrogels. (31st March 2022) - Qin, Ying; Mo, Jilong; Liu, Yanhua; Zhang, Song; Wang, Jinlong; Fu, Qiu; Wang, Shuangfei; Nie, Shuangxi
Abstract: Though visualizing perspiration constituents is crucial for physiological evaluation, inadequate material healing and unreliable power supply methods restrict its applications. Herein, a fully flexible self‐powered sweat sensor is fabricated from a cellulose‐based conductive hydrogel to address these issues. The hydrogel electrode is composed of a cellulose nanocomposite polymerized in situ with polyaniline and cross‐linked with polyvinyl alcohol/borax. The cellulose nanocomposites furnish the sweat sensor with tensile and electrical self‐healing efficiencies exceeding 95% within 10 s, a stretchability of 1530%, and conductivity of 0.6 S m −1 . The sweat sensor quantitatively analyzes Na +, K +, and Ca 2+ contents in perspiration, to sensitivities of 0.039, 0.082, and 0.069 mmol –1, respectively, in real time via triboelectric effect and wirelessly transmits the results to a user interface. This fabricated sweat sensor with high flexibility, stability, and analytical sensitivity and selectivity provides new opportunities for self‐powered health monitoring. Abstract : A conductive hydrogel, cross‐linked by nanocellulose and polyvinyl alcohol demonstrating a highly efficient self‐healing ability (10 s) and excellent tensile properties (1530%) is developed. By applying it as a flexible electrode in a self‐powered sweat sensor, and innovatively utilizing triboelectricity as the working principle, the concentration of Na +, K + and Ca 2+ in sweat can be efficiently detected in real time.